Horse vision through two lenses: Tinbergen’s Four Questions and the Five Domains - Roth, Lina S. V.; McGreevy, Paul (Frontiers in Veterinary Science, 2025)
To improve human–horse interactions and reduce the risk of injury, it is essential to adopt an equi-centric perspective that prioritizes how horses perceive their environment. This review focuses on the equine visual system, both because it is the most studied of the horse’s senses and because misunderstandings about how horses see can lead to unsafe or unsustainable handling. By applying two complementary frameworks, namely Tinbergen’s Four Questions and the Five Domains model, we examine equine vision from both a biological and a welfare-oriented perspective. We explore the anatomical and functional features of the horse’s eye, the development and evolution of visual capacities, and how these relate to behavior, performance and welfare, while also challenging common myths. Horses possess visual adaptations that enable them to perceive fine details, detect color, and see in dim light conditions. However, their evolutionary history as a prey species has shaped them to be highly sensitive to unfamiliar shapes and movements which we also need to be aware of. Ultimately, a deeper understanding of how horses process visual information can help correct misunderstandings, guide safer management practices, and support more ethical and effective care.